Adopting Comparative Fiqh Methodology in Islamic Jurisprudence: Facing Contemporary Challenges with Ethical Considerations - Osman, Affa Mohammed Saeed (UIN Sunan Kalijaga Yogyakarta, 2023)
The challenges faced by contemporary Muslim communities are increasingly complex and multifaceted. To address these challenges effectively, there is a growing recognition of the necessity of adopting a comparative methodology within Islamic jurisprudence. The objective of this study is to underscore the importance of incorporating a comparative methodology in Islamic jurisprudence to navigate the diverse and evolving challenges in the modern world. The research employs a multidisciplinary approach, using a qualitative research methods. This study found that the impact of incorporating comparative methodology in Islamic jurisprudence is profound. It promotes relevance, harmony, ethical guidance, and adaptability while fostering consensus, community empowerment, and interdisciplinary engagement. The comparative methodology within Islamic jurisprudence is an indispensable tool for addressing contemporary challenges. It fosters a deeper understanding of diverse perspectives and promotes harmonious coexistence among different schools of thought. By embracing a dynamic and adaptable approach, Islamic law can effectively respond to the multifaceted issues of the modern world while preserving its core values and principles. This research provides practical recommendations for scholars, jurists, and policymakers on how to incorporate comparative methodology in addressing contemporary challenges within the framework of Islamic jurisprudence.[Tantangan yang dihadapi oleh masyarakat Muslim kontemporer semakin kompleks dan beragam. Untuk mengatasi tantangan-tantangan ini secara efektif, ada pengakuan yang semakin besar akan perlunya mengadopsi metodologi komparatif dalam fikih Islam. Tujuan dari penelitian ini adalah untuk menggarisbawahi pentingnya menggabungkan metodologi perbandingan dalam yurisprudensi Islam untuk menavigasi tantangan yang beragam dan terus berkembang di dunia modern. Penelitian ini menggunakan pendekatan multidisipliner, menggunakan metode penelitian kualitatif. Penelitian ini menemukan bahwa dampak dari penggabungan metodologi komparatif dalam yurisprudensi Islam sangat besar. Metode ini mendorong relevansi, harmoni, panduan etika, dan kemampuan beradaptasi sambil mendorong konsensus, pemberdayaan masyarakat, dan keterlibatan interdisipliner. Metodologi komparatif dalam fikih Islam adalah alat yang sangat diperlukan untuk menjawab tantangan kontemporer. Metodologi ini menumbuhkan pemahaman yang lebih dalam tentang perspektif yang beragam dan mendorong koeksistensi yang harmonis di antara berbagai mazhab. Dengan merangkul pendekatan yang dinamis dan mudah beradaptasi, hukum Islam dapat secara efektif merespons berbagai isu dunia modern sambil tetap mempertahankan nilai-nilai dan prinsip-prinsip utamanya. Penelitian ini memberikan rekomendasi praktis bagi para cendekiawan, ahli hukum, dan pembuat kebijakan tentang bagaimana menggabungkan metodologi komparatif dalam menjawab tantangan kontemporer dalam kerangka yurisprudensi Islam.]